The Effect of Honey on Bacterial Growth, Protein Degradation ,Amino Acids Contents and Volatile Compounds of Milks at Storage - Khusniati, Tatik; Widyastuti, Yantyati (ANNALES BOGORIENSES, 2005)
Pasteurized milks spoiled at refrigerated storage due to growth of psychrotrophic bacteria. Honey which contain antibacterial and aromatic compounds may be used as supplement to inhibit psychrotrophic bacteria activitiy . To know nutritional and flavor compounds of milks with and without honey, effect of honey on bacterial growth0protein degradation. amino acids and volatile compounds of stored milk were detected. Bacterial growth,protein degradation, amino acids and navor compounds were detected by total plate counts. formol titration,HPLC and GCMS, respectively. The results show that bacterial growth and protein degradations in honey milks were lower than that without honey. Bacterial growth (5.2x10^3 - 9,3x10^6 cfu/mL) and protein degradation (2,37-2.59%) in honey whole milks were lower than that (6.2x10^4 - 6.5x10^7 cfu/mL)(2.54-2.88%) in skim milks,respectively (P<0,05). At 10 days after use by date, changing between amino acids contents in whole milks withand without honey were more significant than that or skim milk (P<0.05);. and volatile compounds percentages in honey whole milks were higher than that without honey. while that in honey skim milks vice versa. Honey caused decreasing bacterial growth and protein degradation, changing aminoi acid contents and producing volatile compounds of stored milk, and honey whole milk were better than honey skim milks. Â